Effects of Resveratrol on Ovarian Morphology, Plasma Anti-Mullerian Hormone, IGF-1 Levels, and Oxidative Stress Parameters in a Rat Model of Polycystic Ovary Syndrome. (August 2015) - Ergenoglu, Mete; Yildirim, Nuri; Yildirim, Alkim Gulsah Sahingoz; Yeniel, Ozgur; Erbas, Oytun; Yavasoglu, Altug; Taskiran, Dilek; Karadadas, Nedim
Objective: To evaluate the effects of resveratrol in a rat model of polycystic ovarian syndrome (PCOS). Study Design: After PCOS model was formed by subcutaneous dihydrotestosterone pellets, rats were randomly divided into 2 groups. The first group (n = 7) was treated with 1 mL/kg/d isotonic saline and the second group (n = 7) was treated with 10 mg/kg/d resveratrol. Seven rats were taken as controls without any medication. Results: Our results showed (1) significant reduction in the number of antral follicle counts ( P < .01); (2) significantly decreased plasma anti-Mullerian hormone and insulin-like growth factor 1 levels ( P < .01 and P < .05, respectively); (3) significantly lower superoxide dismutase activity ( P < .05); and (4) significantly increased glutathione peroxidase content ( P < .01) following resveratrol treatment. Conclusion: Resveratrol appears to be effective in the treatment of PCOS due to its antioxidant properties. Future clinical studies with different dosages might provide useful implementations to our practice.